2005
DOI: 10.1177/154193120504900301
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Meta-Information on Decision-Making in Intelligence Operations

Abstract: Decision-making in complex, dynamic, high-risk environments is clearly challenging. Part of this challenge is due to the presence of qualifiers of information, or meta-information (e.g., staleness, uncertainty, source), that alter a person's information processing, situational awareness, and decision-making. We investigated the influence of meta-information on decision-making in a Military Intelligence Operations (IO) environment using Cognitive Task Analysis (CTA) techniques. We performed a CTA on IO tasks su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Metainformation refers to qualifiers of information, such as the uncertainty associated with the information, the age of the information, and the source of the information (Bisantz et al, 2009;Pfautz et al, 2005). Study 1 indicated that reasoning about metainformation is a key cognitive challenge in intelligence analysis, as analysts must consider not only how to collect information to satisfy an information request but also how to collect credible/reliable-enough information and maximally relevant information, all within the time constraints of the original request.…”
mentioning
confidence: 99%
“…Metainformation refers to qualifiers of information, such as the uncertainty associated with the information, the age of the information, and the source of the information (Bisantz et al, 2009;Pfautz et al, 2005). Study 1 indicated that reasoning about metainformation is a key cognitive challenge in intelligence analysis, as analysts must consider not only how to collect information to satisfy an information request but also how to collect credible/reliable-enough information and maximally relevant information, all within the time constraints of the original request.…”
mentioning
confidence: 99%
“…There are many applications, of belief functions and possibility measures in particular, in which it is misleading to regard a set of probability distributions as a set of hypotheses about the "correct" probabilities, because it is meaningless to talk of "correct" probabilities. 6. On the relationship between Bayesian inference and evidence theory Although many papers discuss the abstract relationships between different approaches to uncertainty management, such papers are less abundant that compare the precision and robustness of different approaches in specific application examples.…”
Section: Imprecise Probabilitiesmentioning
confidence: 99%
“…[5,6], few studies discuss basic reliability concepts in high-level fusion-based decision support systems (HLFB-DSS) and applications. In such systems, generic conceptual architectures such as Bayesian networks [7], decision trees, influence diagrams [8], and Bayesian games [9] are frequently adopted, while different approaches to uncertainty management are often combined [2,3,10].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore differentiate our research from a variety of other work addressing intelligence analysis more generally (e.g., (Bodnar, 2005;Pirolli & Card, 2005;Elm et al, 2005)). This general research has been used to guide the development of computational tools to support the Intelligence community, ranging from automated knowledge extraction tools (Boschee, Weischedel, & Zamanian, 2005) to high-level decision support methods (Sticha, Buede, & Rees, 2005;Pfautz et al, 2005a) to numerous data fusion techniques (Gardner & Uhlmann, 2005;Waltz, 1986) to particular display and interface designs (Horn, 2005;Pfautz et al, 2005b). This research has also led to the development of methodologies and metrics for evaluating human performance both with and without those tools (Morse, Potts Steves, & Scholtz, 2005).…”
Section: Introductionmentioning
confidence: 99%